2018
DOI: 10.4172/2161-1149.1000240
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Pulse Pressure and Bone Mineral Density in Adult USA Population: Analysis of the National Health and Nutritional Examination Survey

Abstract: Background/Purpose:Accumulating evidence indicates a relationship between Cardiovascular Disease (CVD) and osteoporosis. Hypertension, a known risk factor for CVD is also associated with low Bone Mineral Density (BMD). We hypothesize that Pulse Pressure (PP); a CVD risk factor is associated with BMD.Methods:Data from two consecutive cycles of National Health and Nutritional Examination Survey (NHANES) from 2009–2010 and 2011–2012. Point estimates of demographic variables were calculated using descriptive metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…PP is defined as SBP minus DBP. High PP largely results from large-artery stiffness, while decreased PP is caused by low stroke volume, such as congestive heart failure and aortic valve stenosis ( 33 ). Vascular smooth muscle cells (VSMC) have important roles in regulating arterial stiffness by overproducing various extracellular matrix components (e.g., collagen and elastin), which provide biomechanical, structural integrity, and signaling regulation of the extracellular matrix components to maintain vascular homeostasis ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…PP is defined as SBP minus DBP. High PP largely results from large-artery stiffness, while decreased PP is caused by low stroke volume, such as congestive heart failure and aortic valve stenosis ( 33 ). Vascular smooth muscle cells (VSMC) have important roles in regulating arterial stiffness by overproducing various extracellular matrix components (e.g., collagen and elastin), which provide biomechanical, structural integrity, and signaling regulation of the extracellular matrix components to maintain vascular homeostasis ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 McFarlane and colleagues found that increased pulse pressure was associated with decreased femoral neck bone mineral density (BMD), revealing a relationship between atherosclerosis and osteoporosis risk. 19 Another study found that atrial fibrillation was an independent risk factor for nonaccidental falls. For people younger than 81 years of age, the risk of nonaccidental falls was 2.5 times higher for those with a history of atrial fibrillation than those without it, and this may be related to reduced cardiac output, bradycardia, and orthostatic hypotension caused by atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pulse pressure is associated with atherosclerosis and is a predictor of the risk of cardiovascular disease 18 . McFarlane and colleagues found that increased pulse pressure was associated with decreased femoral neck bone mineral density (BMD), revealing a relationship between atherosclerosis and osteoporosis risk 19 . Another study found that atrial fibrillation was an independent risk factor for nonaccidental falls.…”
Section: Discussionmentioning
confidence: 99%